Cerium oxide particles, their manufacturing process and their use in chemical mechanical polishing - Patents.com

JP2024513308A5Active Publication Date: 2025-02-19RHODIA OPERATIONS SAS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023553737
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-03-12
Filing Date
2022-03-10
Publication Date
2025-02-19
Estimated Expiration
2042-03-10

AI Technical Summary

Technical Problem

Existing cerium oxide particles for chemical mechanical polishing (CMP) compositions face challenges in achieving high polishing efficiency while minimizing defects and are not easily scalable for industrial use.

Method used

Development of cerium oxide particles with a specific roughness index (RI) of at least 5, calculated by a defined formula, and a cubic morphology, produced through a process involving an aqueous solution of base, nitrate, and organic acid under controlled conditions, followed by heat treatment and optional washing and deagglomeration.

Benefits of technology

The cerium oxide particles exhibit enhanced polishing efficiency and reduced defects, making them suitable for industrial-scale CMP applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention provides a roughness index (RI) of at least 5. [0010] TIFF2024513308000012.tif13170, its manufacturing process and its use in chemical mechanical polishing applications.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to cerium oxide particles and their use as a component of polishing compositions, particularly chemical mechanical polishing (CMP) compositions. The present invention also relates to a method for preparing the cerium oxide particles.

[0002] More specifically, the present invention provides cerium oxide particles that have good abrasive properties when implemented in a CMP composition and a method for preparing such particles that is simple, economical, and easy to carry out on an industrial scale. [Background technology]

[0003] Ceric oxide is commonly used for polishing applications. The development of the electronics industry requires more and more use of compositions for polishing various parts such as disks or dielectric compounds. These compositions, which are usually commercialized in the form of dispersions, must exhibit a certain number of properties. For example, they must provide a high degree of removal of material, which reflects their polishing ability. They must also have as low a defectivity as possible, the term "defectivity" being intended to mean in particular the amount of scratches exhibited by a substrate once treated with the composition. For stability and ease of use, these dispersions usually contain particles of submicron dimensions, i.e. generally less than 300 nm. In addition, the presence of too fine particles in these dispersions reduces their polishing ability, while too large particles can contribute to an increase in defects.

[0004] Thus, several types of cerium oxide particles are known from the prior art that are specifically tailored for CMP applications.

[0005] WO 2015 / 197656 discloses metal-doped cerium oxide particles.

[0006] WO 08043703 discloses a suspension of cerium oxide particles in a liquid phase, said particles being secondary particles having an average size of at most 200 nm, said secondary particles comprising primary particles whose average size is at most 100 nm with a standard deviation of at most 30% of the value of said average size of the primary particles.

[0007] WO 2015 / 091495 discloses a suspension of cerium oxide particles in a liquid phase, the particles comprising secondary particles including primary particles, the secondary particles having a mean size D50 comprised between 105 and 1000 nm with a standard deviation comprised between 10 and 50% of the value of the mean size of the secondary particles, and the primary particles having a mean size D50 comprised between 100 and 300 nm with a standard deviation comprised between 10 and 30% of the value of the mean size of the primary particles.

[0008] It is believed that there is still room for improvement to provide new cerium oxide particles that exhibit improved performance in CMP and methods for the preparation of such particles that are simple, economical and easy to carry out on an industrial scale. Summary of the Invention

[0009] The applicant has created new cerium oxide particles that can solve the above problems.

[0010] One subject of the present invention is therefore cerium oxide particles exhibiting a roughness index (RI) of at least 5. More specifically, the roughness index of a particle is determined according to the following formula:

number

number

[0011] To the best of the inventors' knowledge, the roughness index achieved by the particles of this subject matter of the invention is higher than that of prior art cerium oxide particles, which is believed to contribute to achieving greater polishing efficiency when such particles are used as abrasive particles in CMP compositions or processes.

[0012] The present invention relates to a process for producing the cerium oxide particles of the present invention, comprising at least the following steps: (a) Under an inert atmosphere, (i) an aqueous solution of a base, (ii) NO3 - , Ce III , optionally Ce IV and (iii) an organic acid or a salt thereof to obtain a mixture, wherein the organic acid is a substituted or unsubstituted aryl or heteroaryl carboxylic acid; (b) subjecting the mixture obtained in step (a) to a heat treatment; (c) optionally acidifying the mixture obtained in step (b); (d) optionally washing the solid material obtained at the end of step (b) or (c) with water; (e) optionally subjecting the solid material obtained at the end of step (d) to a mechanical treatment to deagglomerate the particles. The present invention also relates to a process comprising:

[0013] Advantageously, this process makes it possible to prepare the cerium oxide particles of the invention in a simple manner.

[0014] The present invention also relates to cerium oxide particles obtainable or obtainable by the above-mentioned process, a dispersion of the cerium oxide particles of the invention in a liquid medium, the use of said dispersion or the particles of the invention for preparing a CMP composition, a CMP composition comprising said dispersion or said particles, a polishing process in which said CMP composition is used to remove parts of a substrate and the semiconductor containing substrates polished thereby. [Brief description of the drawings]

[0015] [Figure 1-4] 1 is an image of a particle of the present invention as observed by transmission electron microscopy. [Diagram 5] 1 is an image of prior art cerium oxide particles as viewed by transmission electron microscopy. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The photographs were obtained with a JEM-1400 (JEOL) instrument operating at 120 kV.

[0017] In the present disclosure, the expression "comprised in" is to be understood as being inclusive.

[0018] In the context of the particles of the invention, the term "cerium oxide" means cerium(IV) oxide, also known as ceric oxide. Cerium oxide generally has a purity of at least 99.8% by weight, based on the weight of the oxide. Cerium oxide is generally crystalline ceric oxide. Some impurities other than cerium may be present in the oxide. The impurities may come from the raw materials or starting materials used in the preparation process of the cerium oxide. The total proportion of impurities is generally less than 0.2% by weight, based on the cerium oxide. Residual nitrates are not considered as impurities in this application.

[0019] The expression "dispersion", in relation to the dispersion of cerium oxide particles of the present invention, denotes a system consisting of solid, finely divided cerium oxide particles of submicron size stably dispersed in a liquid medium, said particles optionally also containing residual amounts of bound or adsorbed ions, such as ions of nitrate or ammonium.

[0020] The invention will now be described in more detail according to its different embodiments.

[0021] As explained previously, one subject of the present invention is cerium oxide particles exhibiting a roughness index (RI) of at least 5. More specifically, the roughness index of the particles of the present invention may range from 5 to 20, in particular from 6 to 17, and more particularly from 7 to 14.

[0022] The particle roughness index (RI) is calculated according to the following formula:

number

number

[0023] The TEM size is the effective average size of the particles, such as that measured on a large number of particles, at least 80, preferably at least 90, more preferably at least 100, to obtain a statistical analysis. The measurement is usually performed on one or more photographs of the same sample of cerium oxide particles. The particles retained are preferably those whose image is well visible on the photograph. According to an embodiment in which the particles have a cubic shape, as will be detailed later, the number of particles retained that exhibit four sides having substantially the same length and that adjacent sides of these four sides form an angle substantially equal to 90° corresponds preferably to at least 80.0%, more particularly at least 90.0%, even more particularly at least 95.0% of the particles. Some of the particles may exhibit some defects either on their surface and / or on one of their corners. These particles can nevertheless be retained in the statistical analysis.

[0024] The specific surface area (SSA) can be measured for a powder of cerium oxide particles by nitrogen adsorption according to the Brunauer-Emmett-Teller method (BET method). This method is disclosed in the standard ASTM D 3663-03 (reapproved in 2015). This method is also described in the periodical "The Journal of the American Chemical Society, 60, 309 (1938)". The specific surface area can be measured automatically on a Micromeritics instrument TriStar 3000 according to the manufacturer's guidelines. Before the measurement, the sample in powder form shall be degassed under static air by heating at a temperature of at most 210°C in order to remove the adsorbed species.

[0025] The measurement of the BET specific surface area makes it possible to calculate the SSA size according to the formula given above. For a given SSA, the formula gives the theoretical size of a cerium(IV) oxide particle, assuming that the particle is spherical. The ratio TEM size / SSA size is therefore an indicator of the roughness of the particle. The higher this ratio, the higher the roughness of the particle. Cerium oxide particles with an increased roughness index are considered to have improved efficiency when used in polishing processes such as CMP.

[0026] According to one preferred embodiment, the cerium oxide particles of the invention are substantially cubic, and as far as the inventors are aware, the combination of the specific roughness index of the particles and their specific cubic morphology contributes to achieving improved results of CMP with them compared to conventional cerium oxide particles (i.e., which are not cubic and do not exhibit the required roughness index).

[0027] To recognize their cubic morphology, the particles can be observed on photographs obtained by TEM (Transmission Electron Microscopy). The observation of the photographs must be carried out at a size and with an apparatus that allows a clear identification of the shape of the particles. It is therefore preferable to clearly identify the particles individually. The size used for the observation can range, for example, from 25K to 250K. A magnification of 150K can be used. The model JEM 1400 from Jeol, operating at 120 kV, is particularly suitable.

[0028] Images obtained by TEM of such "cubic" cerium oxide particles show four sides having substantially the same length. Moreover, the images are such that adjacent sides of these four sides form an angle substantially equal to 90°. The angle formed by adjacent sides of these four sides may be comprised between 88° and 92° or between 89° and 91°.

[0029] According to one embodiment, the cerium oxide particles of the invention may exhibit an average size that is equal to or greater than 30 nm. In many cases, the particle size is equal to or greater than 70 nm. The cerium oxide particles of the invention may exhibit an average size that is equal to or less than 500 nm. In many cases, the particle size is equal to or less than 300 nm, in particular equal to or less than 150 nm. In one aspect, the cerium oxide particles of the invention may exhibit an average size comprised between 120 and 300 nm, in particular between 125 and 270 nm, more in particular between 130 and 250 nm, even more in particular between 140 and 240 nm. The average size is preferably measured from a TEM image. This measurement is preferably carried out on at least 80 particles.

[0030] According to one embodiment, the cerium oxide particles of the invention may exhibit a specific surface area comprised between 35 and 100 m2 / g, more particularly between 38 and 80 m2 / g, more particularly between 40 and 70 m2 / g and even more particularly between 42 and 60 m2 / g, the specific surface area being measured on the powder by nitrogen adsorption according to the Brunauer-Emmett-Teller method (BET method).

[0031] In a particular embodiment, the specific surface area is between 15 and 100 m2 / g, more particularly between 22 and 70 m2 / g.

[0032] According to one embodiment, the cerium oxide particles of the invention may exhibit a carbon weight ratio ranging from 0.001% to 5% by weight, in particular from 0.1% to 2.5% by weight. The carbon trace may be the footprint of the synthesis method used to prepare the particles, which requires a specific organic acid. The dosing of elemental carbon may be performed by using a carbon and sulfur analyzer, such as a Horiba EMIA 320-V2.

[0033] In another embodiment, the present invention provides a cerium oxide particle exhibiting a Roughness Index RI of at least 2.4, in particular at least 3.5, RI being calculated according to the formula:

number

number

[0034] In certain embodiments, the roughness index RI in this aspect is less than 5.

[0035] To the best of the inventors' knowledge, the carbon weight ratio in the cerium oxide particles according to this embodiment contributes to the compatibility of the cerium oxide particles with other components of dispersions and polishing compositions commonly used for CMP applications.

[0036] The cerium oxide particles according to this embodiment are generally characterized in that the particles are substantially cubic, the characterization of the cubic shape, particle size and specific surface area of ​​this embodiment being as described above.

[0037] The present invention relates to a process for producing the cerium oxide particles of the present invention, comprising at least the following steps: (a) Under an inert atmosphere, (i) an aqueous solution of a base, (ii) NO3 - , Ce III , optionally Ce IV and (iii) an organic acid or a salt thereof to obtain a mixture, wherein the organic acid is a substituted or unsubstituted aryl or heteroaryl carboxylic acid; (b) subjecting the mixture obtained in step (a) to a heat treatment; (c) optionally acidifying the mixture obtained in step (b); (d) optionally washing the solid material obtained at the end of step (b) or (c) with water; (e) optionally subjecting the solid material obtained at the end of step (d) to a mechanical treatment to deagglomerate the particles. The present invention also relates to a process comprising:

[0038] It is advantageous to use salts and components of high purity. The purity of the salt may be at least 99.5% by weight, more particularly at least 99.9% by weight.

[0039] An aqueous solution of a base (i) is used in step (a). Hydroxide type products can in particular be used as bases. Alkali metal or alkaline earth metal hydroxides and aqueous ammonia can be mentioned. Secondary, tertiary or quaternary amines can also be used. The aqueous solution of the base can also be degassed beforehand by bubbling with an inert gas.

[0040] The amount of base used in step (a), expressed in molar ratio base / total Ce, is preferably comprised between 4 and 10, preferably between 5 and 8.

[0041] No.3 - , Ce III and optionally Ce IV An aqueous solution (ii) containing cerium is used in step (a). Nitrate or cerium can in particular be used to prepare the solution. Ce IV When Ce is present in aqueous solution, IV The molar ratio of Ce / total is preferably comprised between 1 / 500000 and 1 / 4000. This molar ratio may in particular be between 1 / 6000 and 1 / 4000. IV / total Ce molar ratios can be used.

[0042] An aqueous solution of ceric nitrate obtained by reacting nitric acid with hydrated ceric oxide may be used in the preparation process. III Cation is Ce IVIt is conventionally prepared by reaction of a solution of a cerous salt with aqueous ammonia in the presence of aqueous hydrogen peroxide to convert it to a cation. It is also particularly advantageous to use a ceric nitrate solution obtained according to the method of electrochemical oxidation of a cerous nitrate solution as disclosed in French patent FR 2 570 087. The ceric nitrate solution obtained according to the teachings of French patent FR 2 570 087 can exhibit an acidity of approximately 0.6N.

[0043] Ce IV When present in step (a), may be provided by a salt which may be cerium IV nitrate or ammonium cerium nitrate.

[0044] No.3 - / Ce III The amount of nitrate ions in the aqueous solution used in step (a), expressed as a molar ratio, is generally between 1 / 3 and 5 / 1. The acidity of the aqueous solution used in step (a) is preferably comprised between 0.8N and 12.0N.

[0045] A specific organic acid (iii) which is a substituted or unsubstituted aryl or heteroaryl carboxylic acid or its salt is used in step (a). The substituted or unsubstituted aryl group is preferably a substituted or unsubstituted phenyl group. The substituted or unsubstituted heteroaryl group is preferably a substituted or unsubstituted heterophenyl group.

[0046] According to one embodiment, the organic solvent is substituted. Examples of substituents include halogen, lower alkyl (i.e. alkyl groups having less than 6 carbon atoms), aryl, alkoxy, hydroxyl, amino, alkylamino, arylamino, alkylsulfinyl, alkylsulfonyl, arylsulfinyl and arylsulfonyl. A preferred substituent is a hydroxyl group. One or more substituents may be present in an aryl or heteroaryl group. Preferably, only one substituent is present therein, and is preferably a hydroxyl group. According to another alternative embodiment, the organic acid is unsubstituted.

[0047] According to one embodiment, the organic acid is a heteroaryl carboxylic acid. The heteroatom portion of said heteroaryl group can include, inter alia, S, O and / or N atoms. One or more heteroatoms can be part of said heteroaryl group. Heteroaryl groups preferably have at least one N atom, more preferably only one N atom. A suitable heteroaryl group in the framework of the present invention can include a pyridyl group. According to another alternative embodiment, the organic acid is an aryl carboxylic acid.

[0048] According to one particular embodiment, the organic acid is an unsubstituted heteroaryl carboxylic acid, preferably an unsubstituted heterophenyl carboxylic acid. The heteroatom portion of the unsubstituted heteroaryl group can include S, O and / or N atoms. One or more heteroatoms can be part of the heteroaryl. The heteroaryl group preferably has at least one N atom, more preferably only one N atom, and is preferably a pyridyl group. The suitable unsubstituted heteroaryl carboxylic acid for carrying out the process of the present invention can include, inter alia, picolinic acid.

[0049] According to another particular embodiment, the organic acid is a substituted aryl carboxylic acid, preferably a substituted phenyl carboxylic acid. Examples of the substituents of the aryl group include halogen, lower alkyl (i.e. alkyl groups having less than 6 carbon atoms), aryl, alkoxy, hydroxyl, amino, alkylamino, arylamino, alkylsulfinyl, alkylsulfonyl, arylsulfinyl and arylsulfonyl. The preferred substituent of the aryl group is hydroxyl. One or more substituents may be present in the aryl group. Preferably, only one substituent is present therein, and is preferably a hydroxyl group. The suitable substituted aryl carboxylic acid for carrying out the process of the present invention may include, inter alia, 4-hydroxybenzoic acid.

[0050] Suitable salts of the above organic acids include ammonium salts.

[0051] According to one embodiment, the organic acid is in the form of an aqueous solution. The concentration of the organic acid in the aqueous solution may range, for example, from 1 to 20% by weight, in particular from 2 to 10% by weight, more particularly from 3 to 7% by weight. According to another embodiment, pure, i.e. undiluted, organic acid is used.

[0052] The components (i), (ii) and (iii) contacted in step (a) to form the mixture can be contacted in any order. In particular, according to one embodiment, an aqueous solution of a base (i) and an organic acid (iii) are contacted with each other, and the resulting mixture is contacted with an aqueous solution (ii) containing cerium nitrate. In such a case, pure (i.e. undiluted) organic acid (iii) can be used, since the solution of the base (i) is already in the form of an aqueous solution. Contacting the mixture of (i) and (iii) with (ii) can preferably include adding (ii) to the mixture under stirring and / or bubbling with an inert gas.

[0053] According to an alternative embodiment, an aqueous solution (ii) containing cerium nitrate and an aqueous solution (i) of a base are contacted with each other and the resulting mixture is contacted with an organic acid (iii). In such a case, the organic acid (iii) can be used in the form of its aqueous solution. The contacting of (ii) with (i) can preferably include adding (ii) to (i) under stirring and / or inert gas bubbling.

[0054] The organic acid (iii) may be used in a concentration ranging from 0.11 to 245 mmol / L, in particular from 0.5 to 150 mmol / L, more in particular from 1 to 100 mmol / L, more in particular from 2 to 50 mmol / L, relative to the total volume of the mixture obtained in step (a). This range is particularly suitable for forming well-defined particles.

[0055] The amount of free oxygen in the mixture should be carefully controlled and minimized. To this end, one or more of the components (i), (ii) and (iii) used and / or the resulting mixture can be degassed by bubbling with an inert gas. The term "inert gas" or "inert atmosphere" is intended to mean an atmosphere or gas that does not contain oxygen, the gas can be, for example, nitrogen or argon.

[0056] Step (a) comprises reacting components (i), (ii) and (iii). Step (a) is preferably carried out under an inert atmosphere, in particular either in a closed reactor or in a semi-closed reactor swept with an inert gas. The contacting is generally carried out in a stirred reactor.

[0057] Step (a) is generally carried out at a temperature comprised between 5° C. and 50° C. This temperature may be between 20 and 25° C.

[0058] Step (b) is the thermal treatment of the reaction medium obtained at the end of the preceding step. It may comprise (i) a heating substep, and (ii) an ageing substep.

[0059] The heating substep (i) may generally comprise heating the medium at a temperature comprised between 75°C and 95°C, more particularly between 80°C and 90°C.

[0060] The maturation substep (ii) may comprise maintaining the medium at a temperature comprised between 75°C and 95°C, more particularly between 80°C and 90°C. The duration of the maturation substep (ii) is comprised between 2 hours and 20 hours. As a rule of thumb, the higher the temperature of the maturation step, the shorter the duration of the maturation substep. For example, when the temperature of the maturation substep is comprised between 85°C and 90°C, for example 88°C, the duration of the maturation substep may be comprised between 2 hours and 15 hours, more particularly between 4 hours and 15 hours. When the temperature of the maturation substep is comprised between 75°C and 85°C, for example 80°C, the duration of the maturation substep may be comprised between 15 hours and 30 hours.

[0061] During step (b), Ce IIICe IV This step can also be carried out under an inert atmosphere, and the statements regarding this atmosphere for step (a) apply here as well. Similarly, the heat treatment can be carried out in a stirred reactor.

[0062] In step (c), the mixture obtained at the end of step (b) can be optionally acidified. This step (c) can be carried out by using nitric acid. The reaction mixture can be acidified with HNO3 to a pH lower than 3.0, more particularly comprised between 1.5 and 2.5.

[0063] In step (d), the solid material obtained at the end of step (b) or step (c) is washed with water, preferably deionized water. This operation makes it possible to reduce the amount of residual nitrates in the dispersion and to obtain the target conductivity. This step can be carried out by filtering the solid from the mixture and redispersing the solid in water. Filtration and redispersion can be carried out several times if necessary.

[0064] In step (e), the solid material obtained at the end of step (d) may be subjected to a mechanical treatment in order to deagglomerate the particles. This step may be carried out by double jet processing or ultrasonic deagglomeration. This step usually results in a sharp particle size distribution and a reduction in the number of large agglomerated particles. According to one embodiment, the cerium oxide particles have been subjected to a mechanical treatment of deagglomeration. According to another embodiment, the cerium oxide particles have not been subjected to a mechanical treatment of deagglomeration.

[0065] After step (e), the solid material may be dried to obtain cerium oxide particles in powder form. After step (e), water or a mixture of water and a miscible liquid organic compound may be added to obtain a dispersion of cerium oxide particles in a liquid medium.

[0066] A further object of the present invention are cerium oxide particles obtainable or obtainable by the process described above.

[0067] The present invention also relates to a dispersion of cerium oxide particles in a liquid medium. The dispersion comprises the cerium oxide particles of the present invention and a liquid medium. The liquid medium can be water or a mixture of water and a water-miscible organic liquid. The water-miscible organic liquid should not cause the particles to precipitate or agglomerate. The water-miscible organic liquid can be, for example, alcohols such as isopropyl alcohol, ethanol, 1-propanol, methanol, 1-hexanol; ketones such as acetone, diacetone alcohol, methyl ethyl ketone; esters such as ethyl formate, propyl formate, ethyl acetate, methyl acetate, methyl lactate, butyl lactate, ethyl lactate. The ratio water / organic liquid can be from 80 / 20 to 99 / 1 (wt / wt).

[0068] The proportion of cerium oxide particles in the dispersion may be comprised between 1.0% and 40.0% by weight, this proportion being expressed as the weight of cerium oxide particles divided by the total weight of the dispersion, and this proportion may be comprised between 10.0% and 35.0% by weight.

[0069] The dispersion may also exhibit a conductivity of less than 300 μS / cm, more particularly less than 150 μS / cm, even more particularly less than 100 μS / cm or 50 μS / cm. The conductivity is measured with a Horiba conductivity meter 9382-10D.

[0070] The cerium oxide particles of the present invention or the dispersion of the present invention can be used to prepare a polishing composition, more particularly a CMP composition. They are used as a component of a polishing composition, more particularly a CMP composition.

[0071] The present invention also relates to a CMP composition. A CMP composition (i.e., a chemical mechanical polishing composition) is a polishing composition used for selective removal of material from the surface of a substrate. It is used in the field of integrated circuits and other electronic devices. In fact, in the manufacture of integrated circuits and other electronic devices, multiple layers of conductive, semiconductive and dielectric materials are deposited on or removed from the surface of a substrate. As layers of material are sequentially deposited on and removed from the substrate, the top surface of the substrate may become non-planar and require planarization. Planarization of a surface (or "polishing" a surface) is the process of removing material from the surface of a substrate to form a generally smooth and flat surface. Planarization is useful for removing undesirable surface topography and surface defects, such as rough surfaces, agglomerated materials, crystal lattice damage, scratches and contaminated layers or materials. Planarization is also useful for forming features on a substrate by removing excess deposited material that was used to fill the features and provide a smooth surface for subsequent levels of metallization and processing.

[0072] The substrate that can be polished with the polishing or CMP composition can be, for example, a silicon dioxide type substrate, glass, semiconductor or wafer.

[0073] The particles of the invention or the dispersion of the invention can be used to prepare a CMP composition. The invention therefore also relates to a CMP composition comprising cerium oxide particles or a dispersion such as defined above.

[0074] The polishing composition or CMP composition usually contains different components other than cerium oxide particles. The polishing composition contains the following components: abrasive particles other than the cerium oxide particles of the cerium oxide particles or dispersions of the invention; and / or - pH adjusters; and / or - surfactants; and / or - rheology control agents, including viscosity enhancers and solidifying agents; and / or - an additive selected from non-ionic polymers, cationic polymers, anionic polymers, quaternary ammonium, silanes, sulfonated monomers, phosphonated monomers, acrylates, starches, cyclodextrins, and combinations thereof; may include one or more of the following:

[0075] The pH of the polishing composition is generally 1 to 6. Typically, the polishing composition has a pH of 3.0 or more. Furthermore, the pH of the polishing composition is typically 6.0 or less.

[0076] The present invention also relates to a method of removing a portion of a substrate, comprising polishing the substrate with a polishing composition such as those described above.

[0077] The invention finally relates to a semiconductor polished by this method.

[0078] To the extent that the disclosures of any patents, patent applications, and publications incorporated herein by reference conflict with the statements of this application to the extent that any term may be unclear, the statements of this application shall control.

[0079] The invention will now be further described in examples, without the intention of limiting it. EXAMPLES

[0080] Example 1 A cerium nitrate solution was prepared by mixing 111.3 g of 2.87 M cerium (III) nitrate, 16.80 g of 68% HNO3, and 3.27 g of deionized water. This solution was placed in a 250 mL semi-closed vessel. Then, cerium (IV) nitrate equivalent to a cerium IV / total cerium molar ratio of 1 / 5000 was added to the cerium nitrate solution. An aqueous ammonia solution was prepared by mixing 74.48 g of 13.35 M ammonia water, 620.90 g of deionized water. This solution was placed in a jacketed 1 L semi-closed reactor and bubbled with N2 gas at a flow rate of 210 L / h under stirring for 1 hour. The above cerium nitrate solution was added to the aqueous ammonia solution in approximately 30 minutes under the same conditions of stirring and N2 bubbling. An organic acid solution was prepared by adding 1.04 g of picolinic acid to 23 g of deionized water, bubbled with N2 gas for 1 h, and then added to the reactor. The temperature of the reaction mixture was warmed to 85° C. in approximately 1 h and maintained under the same conditions of stirring with reduced N2 bubbling flow rate (less than 10 L / h) for approximately 4 h. The reaction mixture was cooled and acidified to pH 2 with 68% HNO3. After decantation, the supernatant was removed and NH4OH was added to the slurry to reach pH 8.

[0081] The reaction mixture was washed with deionized water by centrifugation. The wash was repeated, when the conductivity of the wash was less than 0.04 mS / cm.

[0082] The BET specific surface area measured by nitrogen adsorption was 53.9 m2 / g. The suspension was observed by TEM on approximately 80 particles representative of the suspension, each of the particles was counted and measured. The average particle size was 157 nm with a standard deviation of 23 nm, corresponding to 14% of the average particle size. The SSA size, determined as described herein, was equal to 15, giving a roughness index RI, determined as described herein, of 10.1. The percentage of carbon was measured as %C=1.78% by weight. A TEM photograph of the resulting cubic coarse particles is reported in FIG. 1.

[0083] Example 2 A cerium nitrate solution was prepared by mixing 113.4 g of 2.87 M cerium (III) nitrate, 16.81 g of 68% HNO3, and 3.29 g of deionized water. This solution was placed in a 250 mL semi-closed vessel. Then, cerium (IV) nitrate equivalent to a cerium IV / total cerium molar ratio of 1 / 5000 was added to the cerium nitrate solution. An aqueous ammonia solution was prepared by mixing 75.58 g of 13.35 M ammonia water, 641.44 g of deionized water, and 1.05 g of picolinic acid. This solution was placed in a jacketed 1 L semi-closed reactor and bubbled with N2 gas at a flow rate of 210 L / h under stirring for 1 hour. The above cerium nitrate solution was added to the aqueous ammonia solution in approximately 30 minutes under the same conditions of stirring and N2 bubbling. The temperature of the reaction mixture was warmed to 85° C. in approximately 1 hour and maintained under the same conditions of stirring with reduced N2 bubbling flow rate (less than 10 L / h) for approximately 4 hours. The reaction mixture was cooled and acidified to pH 2 with 68% HNO3. After decantation, the supernatant was removed and NH4OH was added to the slurry to reach pH 8.

[0084] The reaction mixture was washed with deionized water by centrifugation. The wash was repeated, when the conductivity of the wash was less than 0.04 mS / cm.

[0085] The BET specific surface area measured by nitrogen adsorption was 43.1 m2 / g. The suspension was observed by TEM on approximately 80 particles representative of the suspension, and each of the particles was counted and measured. The average particle size was 212.6 nm with a standard deviation of 125 nm, corresponding to 60% of the average particle size. The SSA size, determined as described herein, was equal to 19, giving a roughness index RI, determined as described herein, of 11.0. The percentage of carbon was measured as %C=1.19% by weight.

[0086] A TEM photograph of the obtained cubic coarse particles is reported in FIG.

[0087] Example 3 A cerium nitrate solution was prepared by mixing 222.4 g of 2.87 M cerium (III) nitrate, 33.9 g of 68% HNO3. This solution was placed in a 250 mL semi-closed vessel. Then, cerium (IV) nitrate equivalent to a cerium IV / total cerium molar ratio of 1 / 5000 was added to the cerium nitrate solution. An aqueous ammonia solution was prepared by mixing 133.3 g of 15 M aqueous ammonia, 1298.5 g of deionized water, and 19.9 g of picolinic acid. This solution was placed in a jacketed 2 L semi-closed reactor and bubbled with N2 gas at a flow rate of 100 L / h under stirring for 1 hour. The above cerium nitrate solution was added to the aqueous ammonia solution in approximately 30 minutes under the same conditions of stirring and N2 bubbling. The temperature of the reaction mixture was warmed to 80°C in approximately 1 hour and maintained under the same conditions of stirring with reduced N2 bubbling flow rate (less than 10 L / h) for approximately 4 hours. The reaction mixture was cooled and acidified with 68% HNO3 to pH 2. After decantation, the supernatant was removed and NH4OH was added to the slurry to reach pH 8.

[0088] The reaction mixture was washed with deionized water by centrifugation, and the washing was repeated five times, when the conductivity of the washing solution was less than 0.04 mS / cm.

[0089] The BET specific surface area measured by nitrogen adsorption was 72 m2 / g. The suspension was observed by TEM on approximately 200 particles representative of the suspension, each of the particles was counted and measured. The average particle size was 71 nm with a standard deviation of 19 nm, corresponding to 27% of the average particle size. The SSA size, determined as described herein, was equal to 12, giving a roughness index RI, determined as described herein, of 6.1. The percentage of carbon was measured as %C=4.6% by weight. A TEM photograph of the resulting cubic coarse particles is reported in FIG. 3.

[0090] Example 4 A cerium nitrate solution was prepared by mixing 222.4 g of 2.87 M cerium (III) nitrate, 33.9 g of 68% HNO3. This solution was placed in a 250 mL semi-closed vessel. Then, cerium (IV) nitrate equivalent to a cerium IV / total cerium molar ratio of 1 / 5000 was added to the cerium nitrate solution. An aqueous ammonia solution was prepared by mixing 134 g of 15 M aqueous ammonia, 1296.7 g of deionized water, and 1 g of picolinic acid. This solution was placed in a jacketed 2 L semi-closed reactor and bubbled with N2 gas at a flow rate of 100 L / h under stirring for 1 hour. The above cerium nitrate solution was added to the aqueous ammonia solution in approximately 30 minutes under the same conditions of stirring and N2 bubbling. The temperature of the reaction mixture was warmed up to 80°C in approximately 1 hour and maintained under the same conditions of stirring with reduced N2 bubbling flow rate (less than 10 L / h) for approximately 4 hours. The reaction mixture was cooled and acidified with 68% HNO3 to pH 2. After decantation, the supernatant was removed and NH4OH was added to the slurry to reach pH 8.

[0091] The reaction mixture was washed with deionized water by centrifugation, and the washing was repeated five times, when the conductivity of the washing solution was less than 0.04 mS / cm.

[0092] The BET specific surface area measured by nitrogen adsorption was 25 m2 / g. The suspension was observed by TEM on approximately 150 particles representative of the suspension, each of the particles was counted and measured. The average particle size was 108 nm with a standard deviation of 41 nm, corresponding to 33% of the average particle size. The SSA size, determined as described herein, was equal to 30, giving a roughness index RI, determined as described herein, of 3.6. The percentage of carbon was measured as %C=0.8% by weight. A TEM photograph of the resulting cubic coarse particles is reported in FIG. 4.

[0093] Example 5 A cerium nitrate solution was prepared by mixing 224.4 g of 2.87 M cerium (III) nitrate, 33.9 g of 68% HNO3. This solution was placed in a 250 mL semi-closed vessel. Then, cerium (IV) nitrate equivalent to a cerium IV / total cerium molar ratio of 1 / 5000 was added to the cerium nitrate solution. An aqueous ammonia solution was prepared by mixing 132 g of 15.1 M aqueous ammonia, 1298.9 g of deionized water, and 2.2 g of 4-hydroxybenzoic acid. This solution was placed in a jacketed 2 L semi-closed reactor and bubbled with N2 gas at a flow rate of 100 L / h under stirring for 1 hour. The above cerium nitrate solution was added to the aqueous ammonia solution in approximately 30 minutes under the same conditions of stirring and N2 bubbling. The temperature of the reaction mixture was warmed to 80° C. in approximately 1 hour and maintained under the same conditions of stirring with reduced N2 bubbling flow rate (less than 10 L / h) for approximately 4 hours. The reaction mixture was cooled and acidified to pH 2 with 68% HNO3. After decantation, the supernatant was removed and NH4OH was added to the slurry to reach pH 8.

[0094] The reaction mixture was washed with deionized water by centrifugation, and the washing was repeated five times, when the conductivity of the washing solution was less than 0.04 mS / cm.

[0095] The BET specific surface area measured by nitrogen adsorption was 37 m2 / g. The suspension was observed by TEM on approximately 200 particles representative of the suspension, and each of the particles was counted and measured. The average particle size was 94 nm, with a standard deviation of 53 nm, corresponding to 56% of the average particle size. The SSA size, determined as described herein, was equal to 23, giving a roughness index RI, determined as described herein, of 4.2. The percentage of carbon was measured as %C=1.12% by weight.

[0096] Comparative Example 1 A cerium nitrate solution was prepared by mixing 139.1 g of 2.87 M cerium (III) nitrate, 21.1 g of 68% HNO3, and 4 g of deionized water. This solution was placed in a 250 mL semi-closed vessel. Then, cerium (IV) nitrate equivalent to a cerium IV / total cerium molar ratio of 1 / 5000 was added to the cerium nitrate solution. An aqueous ammonia solution was prepared by mixing 100.5 g of 13.35 M ammonia water and 795.5 g of deionized water. This solution was placed in a jacketed 1 L semi-closed reactor and bubbled with N2 gas at a flow rate of 210 L / h under stirring for 1 hour. The above cerium nitrate solution was added to the aqueous ammonia solution in approximately 30 minutes under the same conditions of stirring and N2 bubbling. The temperature of the reaction mixture was warmed up to 85°C in approximately 1 hour and maintained under the same conditions of stirring with reduced N2 bubbling flow rate (less than 10 L / h) for approximately 4 hours. The reaction mixture was cooled and acidified with 68% HNO3 to pH 2. After decantation, the supernatant was removed and NH4OH was added to the slurry to reach pH 8.

[0097] The reaction mixture was washed with deionized water by centrifugation. The wash was repeated, when the conductivity of the wash was less than 0.04 mS / cm.

[0098] The BET specific surface area measured by nitrogen adsorption was 16.8 m2 / g. The suspension was observed by TEM on approximately 150 particles representative of the suspension, each of the particles was counted and measured. The average particle size was 87 nm, with a standard deviation of 21 nm, corresponding to 24% of the average particle size. The SSA size, determined as described herein, was equal to 50, giving a roughness index RI, determined as described herein, of 1.7. The TEM photograph is reported in FIG. 5.

Claims

1. 1. A method for producing cerium oxide particles comprising the steps of: (a) under an inert atmosphere, (i) an aqueous solution of a base, (ii) NO 3 - , Ce III , optionally Ce IV and (iii) an organic acid or a salt thereof to obtain a mixture, wherein the organic acid is a substituted or unsubstituted aryl carboxylic acid or a substituted or unsubstituted heteroaryl carboxylic acid; (b) subjecting the mixture obtained in step (a) to a heat treatment; (c) optionally acidifying the mixture obtained in step (b); (d) optionally washing the solid material obtained at the end of step (b) or (c) with water; (e) optionally subjecting the solid material obtained at the end of step (d) to a mechanical treatment to deagglomerate the particles. The method includes:

2. 2. The method of claim 1, wherein the organic acid is a substituted or unsubstituted heteroaryl carboxylic acid, preferably an unsubstituted heteroaryl carboxylic acid, more preferably an unsubstituted heteroaryl carboxylic acid having at least one nitrogen atom in the heteroaryl group.

3. The method of claim 1 or 2, wherein the organic acid is picolinic acid.

4. The method according to any one of claims 1 to 3, wherein the heat treatment of step (b) is carried out at a temperature in the range of from 75°C to 95°C.

5. Cerium oxide particles, said particles being substantially cubic and exhibiting a Roughness Index RI of at least 2.4, in particular at least 3.5, RI being determined according to the formula: [0030] (wherein "TEM size" refers to the average size of said particles as measured in a transmission electron microscopy image from at least 80 particles, and "SSA size" refers to the average size of said particles as measured in a transmission electron microscopy image from at least 80 particles, as follows: [0045] where SSA is the BET specific surface area of ​​the particles as measured by nitrogen adsorption, ρ is the density of cerium(IV) oxide, and is 7.22 g / cm 3 is equal to (representing the theoretical average size of the particles according to and said particles exhibit a carbon weight ratio ranging from 0.001% to 5% by weight, in particular from 0.1% to 2.5% by weight.

6. 6. The cerium oxide particle of claim 5, wherein the image of the particle obtained by TEM shows four sides having substantially the same length and wherein adjacent sides of the four sides form an angle substantially equal to 90°.

7. 15 to 100 m 2 / g, more particularly 38 to 80 m 2 / g, more particularly 40 to 70 m 2 / g, and more particularly 42 to 60 m 2 The cerium oxide particles according to claim 5 or 6, characterized in that they have a specific surface area included in the range of 0.1 to 1.0 μm / g.

8. 22 to 70 m 2 The cerium oxide particles according to claim 7, characterized in that they have a specific surface area of ​​1 / g.

9. Cerium oxide particles according to any one of claims 5 to 8, characterized in that they exhibit an average size of 30 to 500 nm, in particular 70 to 300 nm, said average size being determined from TEM images.

10. 10. Cerium oxide particles according to claim 9, characterized in that they exhibit an average size comprised between 120 and 300 nm, in particular between 125 and 270 nm, more in particular between 130 and 250 nm, even more in particular between 140 and 240 nm, said average size being determined from TEM images.

11. Cerium oxide particles according to any one of claims 5 to 10, obtainable by the method according to any one of claims 1 to 4.

12. A dispersion of cerium oxide particles according to any one of claims 5 to 11 in a liquid medium.

13. 13. The dispersion according to claim 12, exhibiting a conductivity of less than 300 μS / cm, more particularly less than 150 μS / cm, even more particularly less than 100 μS / cm or 50 μS / cm.

14. Use of cerium oxide particles according to any one of claims 5 to 11 or of a dispersion according to claim 12 or 13 for the preparation of a polishing composition, more particularly a CMP composition.

15. A polishing composition comprising the cerium oxide particles according to any one of claims 5 to 11 or the dispersion according to claim 12 or 13.

16. 20. A method of removing a portion of a substrate, comprising polishing the substrate with the polishing composition of claim 15.